PERKAWINAN ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA - Dina Tsalist Wildana; Irham Bashori Hasba (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2016)
Marriage at the age of children still occur in some areas. Not only in Indonesia, in some areas is still high number of early marriages. Indonesia has had a regulation on the protection of children. But on the other hand the marriage at the age of children is still high even ranked second in Southeast Asia after Cambodia. This obviously shows that regulation owned does not run optimally. This article will discuss about some children's rights that are violated by the existence of early marriage. Despite showing some of the negative effects of marriage on the age of the child but at the end of this writing offers several formulations so that children in the age of marriage is not so much seized the rights of the child.Perkawinan di usia anak masih marak terjadi di beberapa wilayah. Tidak hanya di Indonesia, di beberapa wilayah masih tinggi angka perkawinan dini.Di Indonesia telah memiliki regulasi tentang perlindungan anak. Namun disisi lain perkawinan di usia anak masih tinggi bahkan menduduki peringkat ke 2 se Asia Tenggara setelah Kamboja. Hal ini jelas menunjukkan regulasi yang dimiliki tidak berjalan optimal. Pada tulisan ini akan membahas tentang beberapa hak anak yang dilanggar dengan adanya perkawinan dini. Kendati menunjukkan beberapa dampak negatifdari perkawinan di usia anak namun di akhir tulisan ini menawarkan beberapa formulasi agar perkawinan di usia anak tidak begitu banyak menyita hak-hak anak.